Thermo-economic analysis of a novel hydrogen production system using medical waste and biogas with zero carbon emission. (15th February 2023) - Zhao, Xinyue; Chen, Heng; Zheng, Qiwei; Liu, Jun; Pan, Peiyuan; Xu, Gang; Zhao, Qinxin; Jiang, Xue
Abstract: The low-cost and continuous hydrogen production from waste has recently received much attention. To achieve clean and efficient in-situ resource utilization, this study proposes a novel hydrogen production system using medical waste and biogas with zero carbon emission, composed of plasma gasification, solid oxide fuel cell, steam turbine cycle, and autothermal reforming. The hybrid system is designed as a poly-generation system capable of producing hydrogen, heat, and electricity to self-sustain the energy consumption required to produce hydrogen for the entire plan. And a thermodynamic and techno-economic of the hydrogen production system is investigated. The results show that the hydrogen production process's energy efficiency and exergy efficiency from medical waste and biogas reach 63.20% and 59.15%, higher than the others. In addition, the system can recover its initial cost in 3.25 years, and the net present value of the new scheme is expected to reach 125, 197.65 k over a 25-year lifetime. Highlights: A novel hydrogen production system using medical waste and biogas. Medical waste and animal waste are synergistically treated. The hybrid system can operate under the polygeneration scenario. A high waste-to-hydrogen efficiency can be achieved. A short payback period is achieved with a high net present value.